Editorial (English) - MOta, Maurício (REVISTA QUAESTIO IURIS, 2016)
Editorial for vol. 09-1 (2016) DOI: 10.12957/rqi.2016.21590 The Journal Quaestio Iuris, ranked by MEC / CAPES as Qualis A2, Law, in this volume 09, number 01, the first of the year 2016, now quarterly, is pleased to publish the article Notes on the government of the right, ethics the virtues and human rights, by professor Carlos Ignacio Massini Correas professor of Philosophy of Lawr and Ethics of the University of Mendoza - Argentina and Director of the Institute of Practical Philosophy and Law Humanities at the same institution and Frederick Bonaldo, assistant professor of Methodology and Legal Logic at the Pontifical Catholic University of São Paulo - PUC-SP and PhD student in Philosophy of law at the same institution. In this article Notes on the government of the right, ethics the virtues and human rights is summed up the meaning and origins of the idea of the government of right, knowing its classical sense of the Enlightenment and linking it - which proves necessary – to virtue ethics and the notion of human rights. Thus the complete formula of the common good - the general justice – will cuminate to the rule of law, which is the practical and ethical reason, coupled with the presence of the moral virtues in the rulers and the ruled, and respect for the natural rights of man